Cost considerations for systemic therapy for patients with advanced genitourinary malignancies. Issue 14 (26th March 2018) - Henry, Mark A.; Leung, Andrew; Filson, Christopher P.
Abstract : The rising cost of health care in the United States has been the focus of intense debate within the medical, legal, and legislative arenas, with the cost of cancer care representing an important component. Cost effectiveness is not always easy to define, and there is no standard metric in assessing this measure related to cancer therapies. Significant controversy surrounds exactly what is the appropriate cost per added year of life. This review examines cost, effectiveness, and comparative cost effectiveness of novel systemic therapies for patients with urologic malignancies. Cancer 2018;124:2897‐905. © 2018 American Cancer Society . Abstract : Several novel and effective systemic therapies have been approved for patients with advanced prostate, kidney, and bladder cancer. This review examines cost, effectiveness, and comparative cost‐effectiveness of novel systemic therapies for patients with urologic malignancies.